Diplomacy Conceptualization For The Security State On Mineral Resources In Indonesia - Boy Nurdin (The Islamic Education and Multiculturalism Foundation, 2024)
Diplomacy is considered for the security state on mineral resources in Indonesia since Indonesia is a law country and has many mining sector possibilities which need to be secured, and created in response to reduce negative impact on mineral illegal mining activities which cause many negative results for Indonesia. Therefore, the Indonesia government needs an alternative effort which lines with the principles concluded by this research. By literatrue reviews employed for the investigation on some international practices published by reputable-indexed journals with the same issue, this research performs an information for the armed forces and the leadership of the Ministry of Law and Human Rights. In the absence of a generally accepted definition of